An empirical analysis of the effectiveness of hotel Revenue Management in five-star hotels in Barcelona, Spain. (September 2017) - Rodríguez-Algeciras, Abel; Talón-Ballestero, Pilar
Abstract: Many capacity-limited service industries have been reaping the benefits by employing Revenue Management (RM) concepts and techniques. Its application in the hospitality industry has enabled thousands of hotels worldwide to phase out the traditional hotel management models and to develop new strategies to more effectively manage these properties. This research aims at assessing the level of application of RM in five-star hotels in Barcelona (Spain), which was ranked the number one city in Spain in terms of international tourist arrivals. Thus, this exploratory study examines RM-related variables and analyzes the data obtained from the application of MERMI (Model for Evaluating Revenue Management Implementation in the Hotel Industry) in Barcelona as a case study. In addition, it provides RM practitioners with empirical evidence of the effectiveness of RM in the hospitality industry in Barcelona, useful insight in determining the challenges associated with its implementation and recommendations to improve the applied RM practices. In general terms, the findings are encouraging for the participating hotels because a high level of application of RM is been reached. However, some theoretical and practical aspects of RM performance in these hotels need to be improved in order to obtain better results in the future.